Pacific Asia - Drakakis-Smith, D. W. (Routledge introductions to development., 2002)
An invaluable introduction to the region, this book assesses Pacific Asia both in terms of its historical development and the present global system, placing general development issues in their local contexts. -- Provided by publisher.